Engaging the health sector in climate-resilient WASH development - Hannah Marcus (IWA Publishing, 2023)
The impact of climate change on water, sanitation, and hygiene (WASH) has driven an increased focus on climate-resilient WASH development. Evidence suggests that adaptation in the WASH sector is underway, but the progress is limited in certain domains and the participation of the public health community may be lacking. Using the Lake Victoria Basin (LVB) as a climate vulnerability setting for this analysis, this study aimed to identify factors that impede full engagement of the health sector in climate-resilient WASH development. In-depth semi-structured interviews were conducted with 13 WASH sector stakeholders across lakeside urban centers in Kenya, Uganda, and Tanzania. Several barriers to health sector engagement were identified including factors related to donor-driven financing and priority setting, a relative neglect of climate vulnerabilities associated with sanitation and hygiene, ministerial siloes, and broader systems of adaptation governance which compromise health sector leadership in climate adaptation. These results suggest room for expansion of interdisciplinary collaborations and deepened involvement of the health sector in WASH-related climate adaptation, which starts with addressing these and other barriers to full health sector engagement. HIGHLIGHTS As climate change threatens WASH systems globally, there is an increasing need to mainstream climate adaptation into WASH sector development.; A failure to adapt WASH services to climate-related hazards could have important adverse consequences with regard to human health.; More interdisciplinary collaboration, among other measures, is needed to enhance the involvement of the health sector in WASH-related climate adaptation.;